Wastewater treatment concepts and practices - Hopcroft, Francis J. (New York, [New York] (222 East 46th Street, New York, NY 10017) : Momentum Press, 2015)
This book provides a concise presentation of the fundamental elements of wastewater treatment process design. It shows the reader where various authors and authorities differ in their interpretation of the fundamentals and offers multiple tables of data from which to select appropriate design parameters. This book is intended to be a process design reference book, not a detailed design manual or a textbook suitable for classroom use.
About the author -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on October 25, 2014).
Keywords: Sewage disposal; environmental engineering; process design; reference manual; wastewater treatment